Cvek pulpotomy – revisited. Issue 6 (10th July 2016) - Bimstein, Enrique; Rotstein, Ilan
Abstract: Background/Aim: While some studies support the notion that the time elapsed from coronal fracture and treatment with Cvek pulpotomy in permanent teeth plays an important role in minimizing the possibility of pain and discomfort, microbial pulp invasion, and ensuring pulp and periodontal healing, others consider that neither time between the accident and treatment nor size of exposure is critical if the inflamed superficial pulp tissue is amputated to the level of a healthy pulp. This study compares published data in an attempt to assess whether the outcome of Cvek pulpotomies is affected by these factors. Results and conclusions: Evidence in the literature suggests to treat a permanent tooth with a complicated crown fracture as soon as possible to diminish the possibility of pain and prevent necrosis and infection of the pulp. Delay of treatment by 9 days or less may have minimal effect on the outcome of Cvek pulpotomies. While the literature indicates that pulp exposures of 4 mm or less may have a good prognosis after a Cvek pulpotomy, the prognosis in teeth with pulp exposures of more than 4 mm has not yet been clarified. Although the literature is not conclusive regarding a difference in the outcomes of Cvek pulpotomies in teeth with open or closed apices, it appears that teeth with open apices have a better prognosis. The outcome of a Cvek pulpotomy may be compromised by a luxation injury that diminishes the tooth's blood supply and innervation. A good restoration that prevents bacterial penetration into the tooth is essential for the success of a Cvek pulpotomy.